Glucosamine Synthetase in the Human Gastrointestinal Mucosa in Health and Disease - Goodman, M (1975)
Glucosamine synthetase (L-glutamine-D-fructose-6-phosphate amino-transferase, EC.2.6.1.16) is the cytoplasmic enzyme which catalyses the synthesis of glucosamine-6-phosphate from fructose-6-phosphate and glutamine. It is a rate-limiting step in the biosynthesis of UDP-N-acetyl-glucosamine and probably also of gastrointestinal mucus, which is glycoprotein in composition. Glycoproteins consist of a protein backbone on which are assembled complex carbohydrate side-chains. The first sugar to be attached to the peptide chain in gastrointestinal mucus is N-acetylgalactosamine, and other important sugars are N-acetylglucosamine and the sialic acids. These particular sugars are supplied to the glycoprotein molecule from UDP-N- acetylglucosamine or from sugar nucleotides which are formed from UDP-N-acetylglucosamine. Glucosamine synthetase has previously been measured in experimental animals but there is no published work on its activity in human tissue. The present thesis describes a method for the measurement of glucosamine syn thetase in the human gastrointestinal mucosa. The thesis describes the steps which were necessary to make the method applicable for use with small biopsy specimens. It then deals with the application of this method to various diseases of the gastrointestinal tract, in particular, to disorders in which it has been suggested that there may be abnormalities of mucus production. The enzyme is assayed by incubating an homogenate of the tissue at 37° with fructose-6-phosphate and glutamine and measuring the synthesized glucosamine colorimetrically by the Morgan-Elson reaction. Rectal biopsies, taken through a sigmoidoscope, weigh between 5 and 30 mg, and gastric biopsies taken through a gastroscope are even smaller. The assay was miniaturized so that only 4 mg tissue were required. This was done by scaling down volumes from methods described in the literature and by adjusting the pH and the substrate concentrations to give the maximum yield of glucosamine. These studies were performed with homogenates of the dissected mucosa from the histologically normal cut ends of colectomy specimens for carcinoma. It was found that the optimum concentration of fructose-6-phosphate was 20 mM, that the optimum glutamine concentration was 8 mM, and that the optimum pH was 7.0. The incubation time selected was 3 hours, and gentamicin 100 μml was added to inhibit bacterial contamination. The requirement for 1 mM EDTA was confirmed. The reproducibility of this microassay was demonstrated by a standard deviation of 10-15% in multiple readings of the same tissue homogenate. The units of enzyme activity adopted were /imoles glucosamine synthesized per hour per g wet weight, which was shown to correlate closely with enzyme activity per g tissue protein (r = 0.90). The requirement for only 4 mg tissue meant that only half of a rectal biopsy needed to be used; the other half could be used for diagnostic histology. When mucosa from surgically resected specimens was assayed, larger volumes were used in the assay, which then required a minimum of 10 mg tissue, but the smaller volumes used with 4 mg tissue in fact gave rise to little additional error. The studies in the development of the microassay showed relationships to pH and substrate concentrations that differed from those of glucosamine synthetase in the rat liver, suggesting that the enzyme in the human colonic mucosa was not the same molecule (Appendix B). A normal range for glucosamine synthetase levels in the human colonic mucosa was obtained from the rectal biopsies of 20 patients with the irritable colon syndrome and from the normal cut ends of colectomy specimens of 22 patients with carcinoma of the colon and 3 patients with localized diverticulitis. The range was 13.77 ± 3.97 (S. D.) units. The levels were similar in all regions of the large intestine and there were no differences with regard to age and sex. There was no glucosamine synthetase activity detectable in the submucosa. In the irritable colon syndrome, five patients who complained of excessive mucus in their stools had normal glucosamine synthetase levels. Mucosal glucosamine synthetase levels were lower than normal in panproctocolectomy specimens for ulcerative colitis and Crohn's disease. There was a close correlation between the glucosamine synthetase level and the overall epithelial cell density; the levels were diminished when there was a general depletion of the epithelial cells but not when there was just distortion of the epithelial glands or damage to the surface layer. Provided the overall epithelial cell density was normal, the glucosamine synthetase levels were normal even when the goblet cells themselves were diminished. Severely inflamed mucosa had a slight glucosamine synthetase activity even when the epithelial cells were completely absent, probably due to enzyme activity in the inflammatory cells. In 15 patients in an acute attack of ulcerative colitis who recovered from the attack, the glucosamine synthetase levels in serial rectal biopsies rose to a peak of 23.94 ± 4.12 units and then fell to normal. Five other patients who did not recover from their acute attack did not shown such a peak. In the morphologically normal rectal mucosa of 13 patients with Crohn's disease elsewhere in the bowel, the glucosamine synthetase levels were 20.55 ± 5.20 units, a highly significant elevation above the normal (P < 0.001). This suggests that the entire colonic mucosa is abnormal in Crohn's disease, even though the obvious lesions are focal. In 3 patients with membranous colitis, the glucosamine synthetase levels rose to 36.0, 31.7 and 27.0 units respectively, which were extremely high values. The enzyme was studied in the tumour tissue of 10 cases of carcinoma of the colon. The range of levels was very wide (1.8-29.9 units) but there was no correlation with any histological feature. In 4 of the patients, the glucos amine synthetase levels were also measured in the histologically normal mucosa immediately adjacent to the tumour; these levels were normal. By pooling two adjacent biopsies in each assay, it was possible to measure the enzyme in biopsies taken through a panendoscope from various sites in the stomach and from the duodenal cap. This was done in 7 patients with normal endoscopic appearances or with lesions confined to the oesophagus and in 24 patients with various disorders of the stomach and duodenum. The glucosamine synthetase level in normal gastric mucosa was found to be approximately 10.0 ± 3.0 units in all parts of the stomach. No significant differences were found between patients with a gastric ulcer and patients with a normal stomach. In the duodenal cap, the glucosamine synthetase levels were 14.07 ± 3.11 units in 14 patients with a normal duodenum and 18.77 ± 2.32 units in 7 patients with an active duodenal ulcer, a highly significant difference (P < 0.002). There was no apparent relationship between the glucosamine synthetase level in the stomach or duodenum and the ABO blood group or the secretor status. The enzyme was also measured in portions of jejunal biopsies obtained with the Crosby capsule. In 14 patients with a normal jejunum, the levels were 17.37 ± 6. 60 units. In 22 biopsies from patients with coeliac disease the levels had a lower mean of 12.05 units but there was a large overlap with the normal range. The glucosamine synthetase microassay was shown to be feasible with percutaneous liver biopsies, giving levels of the order of 3-10 units (Appendix C). An attempt was made to miniaturize an assay for another key enzyme in mucus synthesis, glucosamine-6-phosphate N-acetylase, but this was unsuccessful (Appendix D). The in vitro inhibition of glucosamine synthetase in gastric mucosal homogenates by sodium salicylate and phenylbutazone has been reported by Perrey (1968) and adduced as a possible mechanism for the ulcerogenic effect of these drugs. The experiments of Perrey were repeated in gastric and colonic mucosal homogenates for the ulcerogenic drugs acetylsalicylic acid, sodium salicylate and hydrocortisone hemisuccinate and inhibition of glucosamine synthetase was confirmed. However, a similar degree of inhibition was also shown by paracetamol and by gentamicin, which are non-ulcerogenic drugs. This indicates that experiments to demonstrate the mechanism of drug-induced peptic ulceration should include comparisons with non-ulcerogenic drugs.